Ligand-activated EGFR/MAPK signaling but not PI3K, are key resistance mechanisms to EGFR-therapy in colorectal cancer - Xueping Qu; Habib Hamidi; Radia M. Johnson; Ethan S. Sokol; Eva Lin; Cathy Eng; Tae Won Kim; Johanna Bendell; Smruthy Sivakumar; Benjamin Kaplan; Felipe de Sousa e Melo; Andrew Mancini; et al. (Nature Communications)
Abstract Understanding mechanisms of resistance to active therapies is crucial for developing more effective treatments. Here, we investigate resistance to anti-EGFR and anti-VEGF plus chemotherapy treatment in colorectal cancer (CRC) patients from the IMblaze370 trial (NCT02788279). While anti-VEGF does not select for secondary mutations, anti-EGFR leads to simultaneous mutations in EGFR and MAPK, but not PI3K pathway genes. Notably, we observe frequent acquired mutations in the EGFR extracellular but not intracellular domain and that patients with higher baseline expression of EGFR-ligands are prone to acquire resistant mutations. This data reveals a ligand-activated EGFR/MAPK-signaling dependency in CRC. We also observe enrichment for 8q gains in anti-EGFR treated patients, potentially linked to MYC amplification, a finding further supported by baseline expression analysis. This work adds to the evidence supporting broader evaluation of EGFR and pan-KRAS inhibitor combinations in CRC patients. It also underscores the utility of EGFR ligands as anti-EGFR efficacy biomarkers and provides a rationale for developing ligand blockers to complement and/or improve conventional anti-EGFR therapies in CRC.